Soil organic nitrogen priming to nitrous oxide: A synthesis - Daly, Erin J.; Hernandez-Ramirez, Guillermo; Congreves, Kate A.; Clough, Tim; Voigt, Carolina; Harris, Eliza; Ruser, Reiner (Soil biology & biochemistry, 2024)
The priming effect (PE) is the short-term increase or decrease in the rate of soil organic matter mineralization in response to a stimulus, such as the addition of carbon (C) and/or nitrogen (N) to the soil. Literature has generally framed the PE in terms of CO₂ evolved from soil organic carbon mineralization, but fewer publications have focused on how the PE affects the soil N cycle and nitrous oxide (N₂O) production from soil organic N mineralization (SOM-N), despite the potency of N₂O as a greenhouse gas and ability to destroy stratospheric ozone. This review summarizes our current understanding of how the PE can alter the rates of SOM-N mineralization and subsequently amplify, diminish, or maintain N₂O production in and release from soils, henceforth referred to as N₂O priming. Additionally, the concept of process priming, the differential augmentation of N₂O-producing processes (e.g. priming of nitrification) is introduced. Diverse results across studies suggest that the mechanisms of N₂O priming cannot be fully explained by a single hypothesis, and it is currently unclear how significant the contribution of N₂O priming to net N₂O emissions is, but a preliminary estimate suggests that N₂O emissions resulting from priming mechanisms can range from -39 – 76% following C and N amendments compared to a control. To disentangle the complexity of N₂O priming, an expansion of current research efforts is required. The promotion of open data sharing and publication of full datasets will facilitate the development and validation of models that can accurately simulate the complexity of soil N dynamics and account for the feedback effects of climate change on N₂O priming, which is a key research gap. This is particularly the case in under-studied areas such as permafrost-affected soils of arctic, subarctic, and alpine regions, and vulnerable tropical regions, where climate warming may amplify N₂O priming.